Bases conceptuales para una posible sistematización de las teorías de la comunicación - Meléndez Arteaga, Claudio (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
In this theoretical paper a proposal about the organization of communication theories is presented, followed by an analytical demonstration of its possible application. Accordingly, theories are organized into three groups: thematic theories, related to topics which are almost always present in every communicative event; contextual theories, focused mainly in the diverse settings in which communication, either interpersonal or mediated, takes place, and the general theories that are useful as an attempt to understand the global nature of communication. The demonstration about the functioning of this proposal involves formally an analysis about the interrelationship among three specific instances of manifestation of each of these theories: language in use, as a theme, the communicative contexts and the systemic nature of communication.
Keywords: Communication theory; thematic theories; contextual theories; general theories; systems theory; topic; coherence; speech acts; cooperative principle; monitoring